Mindful Learning melalui Permainan Tradisional Batewah untuk Mengenalkan Budaya Lokal Banjarmasin pada Anak Usia Dini - Maulidha Maulidha; M. Agus Safrian Nur; Rizki Nugerahani Ilise (JURUSAN PENDIDIKAN GURU PENDIDIKAN ANAK USIA DINI, 2026)
This study aims to describe the application of mindful learning through the traditional Batewah game in introducing Banjarmasin local culture to early childhood learners. This research employed a qualitative approach with a narrative study design. The participants were a Group B teacher teaching children aged 5-6 years and early childhood learners involved in Batewah-based learning activities at PAUD IT Nurul Fikri Banjarmasin. Data were collected through observation, interviews, and documentation, and were analyzed narratively through data reduction, data display, and conclusion drawing. The findings indicate that the Batewah game can serve as a conscious, active, enjoyable, and contextual learning medium. Children demonstrated improved attention, turn-taking ability, emotional regulation, cooperation, rule compliance, and respect for peers. Moreover, Batewah helped children recognize Banjar local culture through direct experience, regional language use, game rules, and social values such as togetherness, sportsmanship, responsibility, and patience. The study concludes that mindful learning based on the traditional Batewah game has potential as an early childhood learning strategy that supports children’s holistic development while preserving local cultural identity.